Both Systemic and Intra-articular Immunization with Citrullinated Peptides Are Needed to Induce Arthritis in the Macaque - Bitoun, Samuel; Roques, Pierre; Larcher, Thibaut; Nocturne, Gaétane; Serguera, Che; Chrétien, Pascale; Serre, Guy; Grand, Roger Le; Mariette, Xavier (Frontiers in Immunology, 2017)
Objectives Anti-citrullinated peptides antibodies (ACPAs) have high specificity for the diagnosis of rheumatoid arthritis (RA), but their role in the pathophysiology is not fully established. The main genetic risk factor for RA, the shared epitope in major histocompatibility complex class II, is associated with ACPAs. Among non-human primates, 8% carry the shared epitope called H6 haplotype, and being similar to humans, are ideal candidates to study the role of ACPAs in RA. The goal of this study was to develop a macaque model of RA based on immunization against citrullinated peptides to generate an ACPA-mediated model of arthritis. Methods Cynomolgus macaques were immunized with 4 citrullinated peptides from vimentin, fibrinogen and aggrecan, known to induce T-cell response in RA patients, and received an intra-articular (IA) boost with the same 4 citrullinated peptides pooled. Results In the macaque, the T-cell response was specific to citrullinated peptides. Antibodies generated in response to immunization were cross-reactive between the citrulline and arginine peptides. The presence of the H6 haplotype did not affect the magnitude of the immune response. Since no clinical response observed, macaques received an IA boost with the same 4 peptides pooled and incomplete Freund’s adjuvant, which led to a prolonged neutrophil-rich mono-arthritis, preferentially in H6-positive animals. Conversely, animals boosted with IFA alone presented only transient mono-arthritis. Conclusion This 2-hit model of prolonged mono-arthritis mimics what could happen in RA. Despite the limited number of joints with disease in the macaque model, the model appears unique to study the events occurring during the pre-clinical phase of RA, from immunization against citrullinated peptides to the clinical appearance of disease.